Determination and Removal of Potentially Toxic Elements by Phragmites australis (Cav.) Trin. ex Steud. (Poaceae) in the Valles River, San Luis Potosí (Central Mexico) - José Angel Montes-Rocha; Rocío del Carmen Diaz-Torres; Angel Josabad Alonso-Castro; César Arturo Ilizaliturri-Hernández; Leticia Carrizales-Yáñez; Candy Carranza-Álvarez (Plants)
The contamination of rivers by potentially toxic elements (PTEs) is a problem of global importance. The Valles River is Ciudad Valles’ (Central Mexico) main source of drinking water. During the four seasons of the year, water samples (n = 6), sediment samples (n = 6), and Phragmites australis plants (n = 10) were taken from three study sites selected based on the presence of anthropogenic activities in the Valles River. A graphite atomic absorption spectrophotometer estimated elements in the water, and an energy-dispersive X-ray fluorescence spectrometer quantified elements in sediments and plant samples. Phragmites australis accumulated metal(loid)s mainly in the roots during all seasons of the year. Water samples from all sites recorded PTEs (As, Pb, Cd, and Hg), with primary sources identified as the sugar industry, urban and industrial wastewater, and the combustion of fossil fuels. Sediment samples showed concentrations of Hg, Mn, Ni, Zn, Pb, V, Cu, Cr, and Cd, attributed to agricultural practices, industrial activity, and urbanization. P. australis is an alternative for in situ phytoremediation because this macrophyte can bioaccumulate different elements in its roots, such as Mn, Rb, V, Sr, Cu, Zn, Pb, Ni, and As.